When Does Pre‐IPO Financial Reporting Trigger Post‐IPO Legal Consequences?1. (7th July 2015) - Billings, Mary Brooke; Lewis‐Western, Melissa Fay
Abstract: Prior research suggests that the fear of litigation precludes most managers from manipulating earnings in the initial public offering (IPO) setting. Yet, managers' restraint is perhaps unwarranted: research has not yet linked instances of aggressive pre‐IPO reporting to increased litigation risk. This paper investigates when aggressive IPO reporting triggers legal consequences. Examining 2, 037 IPOs, we find that even when ex post evidence indicates the presence of earnings inflation, litigation is more likely to occur when investors have relied on the suspect earnings during the pricing process. Why might investors rely on some firms' abnormal accruals when valuing the IPO and yet discount the abnormal accruals of other firms? Our analyses suggest that IPO investors incorporate abnormal accrual information into IPO prices in situations where accruals are more likely to reflect information and where other sources of information to help investors make pricing decisions are lacking or are less reliable. In these situations, we find that abnormal accruals do positively correlate with future performance, validating investors' use of this information when pricing these offerings. Yet, when ex post performance reveals that these pre‐IPO abnormal accruals were in fact inflated, we find that litigation emerges to allow harmed shareholders to recover losses incurred dating back to the pricing process—importantly, investors are only harmed if they used those abnormal accruals in pricing the IPO. Collectively, our evidence indicates that litigation in response to earnings inflation does indeed surface in the IPO setting—but only when investors need it to settle the score.